ADMINISTRATIVE SERVICE QUALITY AND USER SATISFACTION AT THE “MANUEL SEOANE CORRALES” PUBLIC HIGHER TECHNOLOGICAL INSTITUTE - Caller Luna, Martha Alicia (2025)
Currently, the demands and requirements of users have changed, and they seek a quality service to be satisfied; the purpose of this research is to determine the relationship between the quality of administrative service and user satisfaction at the "Manuel Seoane Corrales" Public Higher Technological Institute. The research aimed to explore the satisfaction of students from different study programs with reference to the dimensions of staff, facilities and materials, services provided, and the organization's image. The results of this research may help propose alternatives for improving the administrative services provided by the institute. The study is descriptive-correlation in nature, with a quantitative and non-experimental approach. A survey was conducted with 303 students using the SERVQUAL model. The results showed a direct, moderate-strong correlation between administrative service quality and the dimensions of user satisfaction, with the lowest correlation found in the dimension of facilities/materials and the highest in the staff dimension concerning user satisfaction. This indicates that as the quality of administrative service increases, user satisfaction also increases